A CYTOKINE RESPONSE IN BRUCELLA ABORTUS BOVINE INFECTION: LITERATURE REVIEW - septyana eka rahmawati; RIAN ANGGIA destiawan; novarina sulsia ista'in ningtyas; Mutia Hariani Nurjanah (Universitas Airlangga, 2022)
Brucella Abortus infection in cattle is an infection that has a strategic effect on society, especially the economic sector. This disease is caused by gram-negative bacteria, namely Brucella abortion. Treatment of Brucella Abortus Infection in cattle is still not effective. Therapy based on the immune response caused by Brucella Abortus Infection, especially the cytokine response, is an effective choice considering that each type of cow has a different immune response in dealing with Brucella Abortus Infection. The purpose of writing this literature review is to identify cytokines that play a role in Brucella Abortus Infection in cattle. Method: automated PUBMED database search using keywords “Brucella Abortus Bovine”, “Cytokine”, and “Brucellosis”. Results: 11 articles that are relevant and meet the inclusion criteria to analyze the cytokines that play a role in Brucella Abortus Infection in cattle. Conclusion: Cytokines that play a role in Brucella Abortus infection in cattle are generally IL-1, IL-6, IL-12, IL-8, TNF-α, and IFN-γ.